Makna Fonemik dalam Semantik Arab: Ontologi, Epistemologi, Aksiologi - Romanda, Fharis (Al-Ma‘rifah, 2021)
This study aims to provide an understanding of the phonemic meaning (dalālah ṣawṭīyah) in Arabic semantics. To provide an understanding related to dalālah ṣawṭīyah, this study carries out its research based on a philosophical framework of thought consisting of ontology, epistemology, and axiology. It can be concluded that the discussion of this research broadly discusses the ontology or nature of ṣawṭīyah, its epistemology or method, and the axiology or function of the branch of the discussion of semantics. This research is based on a literature review. In analyzing data obtained from the literature review, this study used qualitative methods. This research has revealed the nature of sound, how sound works, and the function of each sound method in the Arabic interpretation process. This research concludes that the sound in the dalālah ṣawṭīyah has an important role in determining meaning in all language structures starting from Arabic words, phrases, and sentences. The method of sound work in giving meaning to Arabic can be in the form of differences in phoneme sounds, sound stress (al-nabr) in syllables or words, as well as intonation (al-tanghīm) that occurs in a phrase or sentence.